International Osteoporosis Foundation and European Calcified Tissue Society Working Group. Recommendations for the screening of adherence to oral bisphosphonates. - Diez-Perez, A; Naylor, K; Abrahamsen, B; Agnusdei, D; Brandi, M; Cooper, C; Dennison, E; Eriksen, E; Gold, D; Guañabens, N; Hadji, P; Hiligsmann, M; et al. (Springer, 2017)
Background Low adherence to oral bisphosphonates is a common problem that jeopardizes the efficacy of treatment of osteoporosis. No clear screening strategy for the assessment of compliance is widely accepted in these patients. Methods The International Osteoporosis Foundation and the European Calcified Tissue Society have convened a working group to propose a screening strategy to detect a lack of adherence to these drugs. The question to answer was whether the bone turnover markers (BTMs) PINP and CTX can be used to identify low adherence in patients with postmenopausal osteoporosis initiating oral bisphosphonates for osteoporosis. The findings of the TRIO study specifically address this question and were used as the basis for testing the hypothesis. Results Based on the findings of the TRIO study, specifically addressing this question, the working group recommends measuring PINP and CTX at baseline and three months after starting therapy to check for a decrease above the least significant change (decrease of more than 38% for PINP and 56% for CTX). Detection rate for the measurement of PINP is 84%, for CTX 87% and, if variation in at least one is considered when measuring both, the level of detection is 94.5%. Conclusions If a significant decrease is observed the treatment can continue but if no decrease occurs the clinician should reassess to identify problems with the treatment, mainly low adherence